2002
DOI: 10.1006/excr.2001.5460
|View full text |Cite
|
Sign up to set email alerts
|

Clofibrate-Induced Relocation of Phosphatidylcholine Transfer Protein to Mitochondria in Endothelial Cells

Abstract: The phosphatidylcholine transfer protein (PC-TP) is a specific transporter of phosphatidylcholine (PC) between membranes. To get more insight into its physiological function, we have studied the localization of PC-TP by microinjection of fluorescently labeled PC-TP in foetal bovine heart endothelial (FBHE) cells and by expression of an enhanced yellow fluorescent protein-PC-TP fusion protein in FBHE cells, human umbilical vein endothelial cells, and HepG2 cells. Analysis by confocal laser scanning microscopy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 51 publications
4
33
0
Order By: Relevance
“…Observations 6 In a nomenclature revision, Them1 and CACH have been also been renamed acyl-CoA thioesterase 11 (Acot11) and acyl-CoA thioesterase 12 (Acot12), respectively (41). here and by de Brouwer et al (40) have suggested that fluorescent PC-TP fusion proteins are present within the nucleus, which is supported by immunolocalization of the endogenous protein in HEK 293T cells. Considering that PC-TP has no apparent DNA-binding domain, we tested the possibility that it might coactivate or corepress Pax3 transcriptional activity.…”
Section: Discussionsupporting
confidence: 61%
“…Observations 6 In a nomenclature revision, Them1 and CACH have been also been renamed acyl-CoA thioesterase 11 (Acot11) and acyl-CoA thioesterase 12 (Acot12), respectively (41). here and by de Brouwer et al (40) have suggested that fluorescent PC-TP fusion proteins are present within the nucleus, which is supported by immunolocalization of the endogenous protein in HEK 293T cells. Considering that PC-TP has no apparent DNA-binding domain, we tested the possibility that it might coactivate or corepress Pax3 transcriptional activity.…”
Section: Discussionsupporting
confidence: 61%
“…By contrast, PC-TP and Them2 are individually targeted to mitochondria ,where they engage in interactions. Whereas Them2 is enriched in mitochondria ( 8 ), PC-TP is enriched in cytosol but relocalizes to mitochondria in response to selective cell signaling events ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that PCTP may play a role in resupplying the canalicular membrane with biliary PC during bile formation (46) and that PCTP may be regulated by PPAR␣ stimulation both transcriptionally (31) and posttranslationally (47). Moreover, coregulation of PCTP, ABCB4, and biliary PC secretion in humans (13) suggests that PCTP may play a role in bile formation.…”
Section: Discussionmentioning
confidence: 99%